Regulation of apoptosis and interaction with cartilage degeneration in osteoarthritis - Mei, Jiahua; Xiao, Niqin; Xi, Yujiang; Chen, Xin; Zha, Xuezhi; Cui, Lili; Yan, Fei; Xue, Rui; Wang, Yongsen; Ma, Yunshu (Frontiers in Cell and Developmental Biology, 2025)
Osteoarthritis (OA) is a chronic degenerative joint disease, primarily characterized by the degradation of the ECM and cartilage degeneration. Articular cartilage is maintained by chondrocytes, which secrete the ECM, making the stability of these cells crucial for joint function. Research has shown that in the later stages of OA, cartilage cavities form, indicating a decline in chondrocyte function. Chondrocyte death is considered a central feature of cartilage degeneration. Apoptosis, a form of programmed cell death, plays a key role in this process. While controlled apoptosis helps remove damaged chondrocytes and protects the cartilage from injury, excessive apoptosis disrupts the balance of the cartilage microenvironment and accelerates OA progression. Therefore, regulating chondrocyte apoptosis may offer a novel approach for preventing and treating cartilage degeneration. This review examines the apoptosis pathways, the interaction between apoptosis and OA, the key regulatory factors of chondrocyte apoptosis, and analyzes current drug interventions targeting apoptosis in both preclinical and clinical studies. It also discusses the challenges in treating OA and outlines future research directions to guide upcoming studies.